Survival Analysis of the Effect of Season at Calving, Lactation Number and Breeding on Days Open in Dairy Cattle at Khon Khaen Province, Thailand - Taufik, E; Suriyasataphorn, W (Indonesian Journal of Animal and Veterinary Sciences, 2008)
The objective of this study was to evaluate the effect of season at calving, lactation number and breeding on days open (interval between calving and conception) in dairy cattle by using Cox proportional hazards model as a survival analysis method. The data were sampled from 143 cows at 6 farms located in Khon Kaen Province, North-Eastern Thailand and classified as farm identification (FID), cow identification (CID), calving date (CDA), date at last follow up (LAF), percentage of Holstein-Friesian (PHF), lactation number (LAN) and event of interest (1 = conception, 0 = not conception) (event). Time of days open was calculated by subtracting LAF by CDA and CDA was used to determine season of calving. The result showed that based on Kaplan-Meier survivorship percentiles, overall median days open of cattle were at 210, whereas median days open for the cow calved in summer was 231 and 204 for the cow calved in other season. Median days open for the cow calved with one lactation was 226 and 207 for the cow with two lactation and more. Median days open for the cow with percentage of Holstein-Friesian <75% was 211 and 206 for the cow with percentage of Holstein-Friesian >75%. The result from Cox proportional-hazard regression of days open for Khon Khaen dairy cows showed that cows that calved in rainy and winter had a greater chance of 1.28 times and 1.76 times, respectively, of becoming pregnant than those calved in summer, although the difference was insignificant and cows with lactation number two or more were marginally had 1.54 times chance to get pregnant compare to cows with one lactation number, even though this chance was not statistically significant (P = 0.1725), whereas cows with percentage of Holstein Friesian >75% had significantly greater chance 1.17 times more to get pregnant compare to those with percentage of Holstein Friesian <75%. Key Words: Survival Analysis, Cox Proportional Hazard Model, Dairy Cow, Days Open